Exploring the Factors for Marketing Indoor Cycling - Berger, Paul D. (Archives of Business Research, 2019)
In this paper, we use multiple regression and stepwise regression analyses to consider a set of variables to determine what is important in the marketing of, and actual use, of indoor cycling. We find that the importance of music to the consumer, and the importance of cleanliness of the studio to the consumer are key factors in the amount of use a consumer makes of indoor cycling. We also discuss entertainment marketing and the role of sense of community.